2022
DOI: 10.1002/jcp.30827
|View full text |Cite
|
Sign up to set email alerts
|

IPMK modulates hepatic glucose production and insulin signaling

Abstract: Hepatic glucose production (HGP) is crucial for the maintenance of normal glucose homeostasis. Although hepatic insulin resistance contributes to excessive glucose production, its mechanism is not well understood. Here, we show that inositol polyphosphate multikinase (IPMK), a key enzyme in inositol polyphosphate biosynthesis, plays a role in regulating hepatic insulin signaling and gluconeogenesis both in vitro and in vivo. IPMK-deficient hepatocytes exhibit decreased insulininduced activation of Akt-FoxO1 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…In this study, we investigated the hypothesis that IPMK plays a role in HFD-induced insulin resistance. IPMK protein levels were decreased in the liver tissues of mice fed HFD (Jung et al, 2022). Moreover, FFA treatment decreased IPMK protein in PMH in a concentration-and timedependent manner.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In this study, we investigated the hypothesis that IPMK plays a role in HFD-induced insulin resistance. IPMK protein levels were decreased in the liver tissues of mice fed HFD (Jung et al, 2022). Moreover, FFA treatment decreased IPMK protein in PMH in a concentration-and timedependent manner.…”
Section: Discussionmentioning
confidence: 90%
“…It has been shown that IPMK regulates insulin signaling in multiple cell types. We recently reported that the deletion of hepatic IPMK decreased insulin-mediated Akt signaling and aggravated HFD-induced insulin resistance and glucose intolerance (Jung et al, 2022). Moreover, we found a significant decrease in IPMK protein in the liver of insulin-resistant mice subjected to a High-fat diet (HFD) for a long-term period (Jung et al, 2022).…”
Section: Ffa Treatment Reduces Ipmk Protein Levels In Primary Mouse H...mentioning
confidence: 90%
See 2 more Smart Citations
“…On the other hand, inositol polyphosphates (InsPs) are another type of phosphate polymers which have recently been found to have strong metabolic connections with polyP [ 38 , 39 , 40 ]. Recently, enzymes of InsPs metabolism have been related to insulin signaling [ 41 ], insulin resistance, and type 2 diabetes [ 42 ]. Therefore, it is to be expected that differences in plasma polyP levels may be connected with InsPs metabolism.…”
Section: Discussionmentioning
confidence: 99%